2010
DOI: 10.1111/j.1872-034x.2010.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Internal ribosomal entry‐site activities of clinical isolate‐derived hepatitis A virus and inhibitory effects of amantadine

Abstract: HAV IRES derived from clinical isolates have various activities. Bicistronic reporter assay using clinical isolates may be another useful tool for testing antiviral activities like those of amantadine and the new acridines and hydrazones recently reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…It is known that the M2 protein of influenza A virus is a target of amantadine [19]. Furthermore, it has been reported to inhibit HAV IRES-mediated translation and replication by our group and other researchers [2,3,5-8]. …”
Section: Short Reportmentioning
confidence: 85%
See 2 more Smart Citations
“…It is known that the M2 protein of influenza A virus is a target of amantadine [19]. Furthermore, it has been reported to inhibit HAV IRES-mediated translation and replication by our group and other researchers [2,3,5-8]. …”
Section: Short Reportmentioning
confidence: 85%
“…Interestingly, amantadine and IFN also inhibited HAV IRES-mediated translation and HAV replication [2,3,5-8]. Accordingly, we planned to identify more effective strategies for suppressing HAV IRES-mediated translation and HAV replication.…”
Section: Short Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…HAV IRES derived from clinical isolates have shown various activities in in vitro cell culture 5,12. Also complicating this issue is the fact that the definition of acute liver failure differs among different countries 11,14.…”
Section: Introductionmentioning
confidence: 99%
“…The downstream part of 5′NTR represents the internal ribosomal entry site (IRES), which mediates cap-independent translation initiation and is important for HAV replication [9], [10]. 5′NTR of HAV is also known as one of the most highly conserved in the HAV genome sequences, making this region one of the likely candidates for antiviral targets [9], [11]. It was reported that nucleotide variations in the central portion of 5′NTR of HAV may influence the severity of hepatitis A [12].…”
Section: Introductionmentioning
confidence: 99%